Dialectal variation in the Spanish language as a problem of mastering spoken language by Russian-speaking students - O. V. Murashkina (Ибероамериканские тетради)
The article deals with the problem of phonological hearing formation in the process of teaching Spanish as a foreign language. The main difficulty of mastering Spanish phonetics is the diversity of nationalvariants and dialects of the Spanish language, as they represent the varied allophonic picture at the levelof speech.